LECTINS IN THE INVESTIGATION OF CARDIAC MORPHOLOGY AND FUNCTION - Nadraga, B.А.; Sogomonian, Е.А.; Yashchenko, А.М.; Lutsyk, А.D. (World of Medicine and Biology, 2018)
Background. Lectins play a significant role in modern morphological research. At the same time, despite of numerous publications, using lectin histochemistry methods for the investigations of heart, knowledge on remodelling of cardiac tissues carbohydrate determinants under different pathological conditions, including the progression of ischemic disease, post heart attack lesions, as well as possibilities of predicting post- infarction rehabilitation processes is far from complete.The aim of present investigation was to study lectin labeling characteristics of normal human myocardium and that affected by post-infarction cardiosclerosis.Materials and methods. We investigated cardiac muscle samples, excised from left ventricular areas of two men aged 82 and 78, with postmortal diagnosis “post-infarction cardiosclerosis, recurring acute myocardial infarction”. As control specimens were used heart muscle samples of 46 years old man, and of a woman aged 54, who died without evidence of cardiac diseases. The material was collected at the Pathological Department of Lviv Regional Clinical Hospital during scheduled autopsies, with accordance to bioethics rules. Histological material was fixed in 4% neutral formalin and embedded in paraffin due to standard protocol. Sections 5-7 μm thick were stained by haematoxylin and eosin. Carbohydrate determinants of glycoconjugates were detected using wheat germ agglutinin (WGA, specific to DGlcNAc > NeuNAc), Ricinus communis agglutinin (RCA, specific to DGal > NeuNAc), and Laburnum anagyroides bark agglutinin (LABA, LFuc-specific), coupled to horseradish peroxidase. Lectin receptor sites were visualized using diaminobenzidine tetrahydrochloride (Sigma, USA). Microscopy was conducted and pictures taken using Granum R6053 photomicroscope equipped with Echoo-Imager 502000, and the ToupView 3.7 computer program.Results. Haematoxylin and eosin staining of control samples revealed typical structure of cardiac muscle: alternation of muscle fibres with haemocapillars of vascular bed; nuclei of contractile cardiomyocytes demonstrated central localization in within the cells; intercalated discs and cross striations of myofibrils were poorly expressed. Focal islets of connective tissue and lipofuscin inclusions (numerous brown granules in perinuclear localization) – were considered as manifestations of age-related changes. Post-infarction cardiosclerosis was accompanied with hypertrophy of cardiomyocytes in combination with numerous ruptures of muscle fibers with the defects replacement by connective tissue elements – signs of microfocal cardiosclerosis. Perivascular accumulation of connective tissue supplemented with desquamation of vascular bed endothelium, microthrombosis and diapedesis of erythrocytes were also characteristics features of post-infarction cardiosclerotic myocardium. Some contractile cardiomyocytes lost their nuclei, others exposed signs of with karyopyknosis and karyorhexis, encompassing apoptotic conditions in them. Blood in within myocardial vasculature was enriched with lymphoid cells apparently due to reactive changes in the cardiac muscle in response to post-infarction injury. Lectin labels in control samples myocardium were restricted predominantly to plasma membranes of erythrocytes and contractile cardiomyocytes, as well as to perinuclear granularity of the latters, responding to lipofuscin inclusions. It is noteworthy that lipofuscin granules could be visualized without lectin and even diaminobenzidine preincubation, therefore causing false-positive reaction. This observation was not documented in the available literature. In post-infarction cardiosclerotic lesions lectins distinctly labeled stromal elements, including microvascular bed, and tissue detritus. WGA staining additionally demonstrated presence of atypical spindle-shaped endothelial cells in within the blood vessels, exposed strong reactivity with cytoplasmic glycoconjugates of lymphocytes and plasma cells, desorganized fibrous elements of perivascular localization. Appearance of atypical spindle-shaped endothelium, as well as endothelial cells desquamation apparently reflect subsequent steps of these cells hypoxia-related alteration. Lectin labeling was also useful for the demonstration of arterial wall stratification, disintegration of their internal elastic membranes, microthrombotic formations, diapedesis of erythrocytes, edematous conditions of interstitial connective tissue. In our hands WGA and LABA lectins did not react with contractile cardiomyocytes nuclei, and myofibrils were not RCA-positive. These discrepancies with data of others apparently relay on tissue-specific differences of cardiac carbohydrate determinants, as well as on different fixative media and staining protocols used. The obtained data are supplemented with a literature survey on the application of lectin histochemistry methods for the investigation of cardiac morphology and functionConclusions. In comparison with the routine morphological methods, WGA and RCA demonstrated significantly higher selectivity of connective tissue and heart muscle microvascular bed labeling, therefore these same lectins can be recommended as an alternative for quantitative evaluation of cardiosclerotic lesions.
Keywords: lectin histochemistry; human myocardium; post-infarction cardiosclerosis